2019
DOI: 10.1093/gbe/evz130
|View full text |Cite
|
Sign up to set email alerts
|

First Estimation of the Spontaneous Mutation Rate in Diatoms

Abstract: Mutations are the origin of genetic diversity, and the mutation rate is a fundamental parameter to understand all aspects of molecular evolution. The combination of mutation–accumulation experiments and high-throughput sequencing enabled the estimation of mutation rates in most model organisms, but several major eukaryotic lineages remain unexplored. Here, we report the first estimation of the spontaneous mutation rate in a model unicellular eukaryote from the Stramenopile kingdom, the diatom Phaeodactylum tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 105 publications
2
47
0
Order By: Relevance
“…Red data points highlight the observed base pair substitution (BPS) rate of Dictyostelium discoideum from this study with respect to effective population size ( N e ) and nucleotide diversity (θ) ( Flowers et al 2010 ). Black data points correspond to the following additional unicellular eukaryote species for reference: Chlamydomonas reinhardtii ( Smith and Lee 2008 ; Sung et al 2012a ; Ness et al 2015 ); Paramecium biaurelia , Paramecium sexaurelia ( Long et al 2018a ); Paramecium tetraurelia ( Sung et al 2012b ); Ostreococcus tauri ( Krasovec et al 2017 ); Plasmodium falciparum ( Lynch 2010 ; Hamilton et al 2017 ); Saccharomyces cerevisiae ( Schacherer et al 2009 ; Zhu et al 2014 ); Schizosaccharomyces pombe ( Fawcett et al 2014 ; Behringer and Hall 2016a ); Tetrahymena thermophila ( Long et al 2016 ); Phaeodactylum tricornutum ( Krasovec et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Red data points highlight the observed base pair substitution (BPS) rate of Dictyostelium discoideum from this study with respect to effective population size ( N e ) and nucleotide diversity (θ) ( Flowers et al 2010 ). Black data points correspond to the following additional unicellular eukaryote species for reference: Chlamydomonas reinhardtii ( Smith and Lee 2008 ; Sung et al 2012a ; Ness et al 2015 ); Paramecium biaurelia , Paramecium sexaurelia ( Long et al 2018a ); Paramecium tetraurelia ( Sung et al 2012b ); Ostreococcus tauri ( Krasovec et al 2017 ); Plasmodium falciparum ( Lynch 2010 ; Hamilton et al 2017 ); Saccharomyces cerevisiae ( Schacherer et al 2009 ; Zhu et al 2014 ); Schizosaccharomyces pombe ( Fawcett et al 2014 ; Behringer and Hall 2016a ); Tetrahymena thermophila ( Long et al 2016 ); Phaeodactylum tricornutum ( Krasovec et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the two T. rotula , two T. weissflogii and two S. marinoi (MMETSP1039 and MMETSP1040) have π ~0.01, giving N e ~5 million individuals. Furthermore, it was previously reported that several other marine plankton species have N e ~10 million: diatom P. tricornum [42], coccolithophore E. huxleyi [46] and coastal green algae O. tauri [47]. Thus, effective population sizes of plankton species analysed so far are of the order of a few million individuals, which indicates the generality of the finding that marine plankton typically have relatively modest N e , despite astronomically large census population sizes [46].…”
Section: Resultsmentioning
confidence: 99%
“…In P. tricornutum , the mutation spectrum is known [42], so k is readily available. In the case of GC-rich preferred codon, u = 2.21 and v = 1.0, so k = 2.21.…”
Section: Methodsmentioning
confidence: 99%
“…Duckweed estimated highlighted by red box. References: (Ossowski et al 2010;Lynch 2010;Denver et al 2012;Schrider et al 2013;Weller et al 2014;Zhu et al 2014;Venn et al 2014;Keightley et al 2015;Uchimura et al 2015;Yang et al 2015;Farlow et al 2015;Ness et al 2015;Smeds et al 2016;Xie et al 2016;Besenbacher et al 2016 p.;Feng et al 2017;Liu et al 2017;Oppold and Pfenninger 2017;Flynn et al 2017;Krasovec et al 2017Krasovec et al , 2018Krasovec et al , 2019Hanlon et al 2019;Orr et al 2020)…”
Section: Discussionmentioning
confidence: 99%